Molybdenum-tungsten-sulfur alloy film on high temperature resistant substrate and preparation method thereof

Directly prepared two-dimensional molybdenum-tungsten sulfur alloy film on high-temperature resistant substrates through laser direct writing technology, solving the problems of pollution and damage during material transfer in the prior art, and achieving high-quality, large-area molybdenum-tungsten sulfur alloy material The preparation is suitable for high-performance applications of flexible electronic devices.

CN115627453BActive Publication Date: 2024-12-20NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211141768.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-20
Publication Date
2024-12-20
Estimated Expiration
2042-09-20

AI Technical Summary

Technical Problem

The prior art is difficult to directly prepare high-quality, large-area molybdenum-tungsten sulfur alloy materials on high-temperature resistant flexible substrates, and are susceptible to contamination and damage during material transfer, limiting the high performance and low energy consumption applications of flexible electronic devices.

Method used

The two-dimensional molybdenum-tungsten sulfur alloy film is directly prepared on the mica substrate by using laser direct writing technology. The precursor solution is formed by mixing the reaction source and stabilizer in an organic solvent, spin coating and evaporating the substrate face to face, and the laser parameters are adjusted. The treatment was performed to prepare a large area of ​​molybdenum-tungsten sulfur film.

Benefits of technology

It realizes the direct preparation of high-quality, programmable, patterned two-dimensional molybdenum-tungsten sulfur alloy films on high-temperature resistant substrates, avoiding pollution and damage during material transfer, and the material size can reach centimeter level, making the preparation process simple and fast Fast, suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115627453B_ABST
    Figure CN115627453B_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum-tungsten-sulfur alloy film on a high-temperature resistant substrate and a preparation method thereof; mica is used as a substrate, a reaction source and a stabilizer are mixed in an organic solvent to form a precursor solution, the precursor solution is spin-coated on the surface of the mica substrate until the organic solvent evaporates to obtain a precursor film; two mica substrates with precursor films on their surfaces are stacked face to face, and the stacked mica substrates are subjected to laser direct writing treatment using a laser direct writing technique to obtain a two-dimensional molybdenum-tungsten-sulfur alloy film; the parameters of the laser direct writing treatment include: a working distance of 100 to 120 mm; a laser power of 2 to 5 W; a pulse frequency of 20 to 200 kHz; a laser spacing of 1 to 100 μm; and a writing speed of 0.1 to 1 m / s. In the invention, the two-dimensional molybdenum-tungsten-sulfur alloy film can be directly prepared on a high-temperature resistant substrate, so that the material is prevented from being contaminated and damaged during the transfer process, and the prepared material has high quality and a large area, and can be patterned.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano materials, and in particular relates to a molybdenum-tungsten-sulfur alloy film on a high-temperature resistant substrate and a preparation method thereof. Background Art

[0002] Flexible sensors have been widely studied due to their wide application prospects in various flexible electronic products. However, most of the flexible sensors studied so far are only suitable for working at room temperature, and their application at high or low temperatures remains a great challenge. Two-dimensional (2D) transition metal dichalcogenide alloys with adjustable band gaps have broad application prospects in nanoelectronics and optoelectronics, and have become the research focus in the field of flexible electronic devices, bringing new hope for the development of flexible electronics. Since transition metal chalcogenides have a band gap of 1 to 2 eV, it is difficult for a single 2D TMDs to achieve wide-range band regulation and control of charge transfer, while continuous regulation of the band gap can be achieved by preparing ternary alloys. However, flexible electronic devices usually require large areas and high-quality materials, and the complicated processes of manufacturing and integration limit the practical application of 2D TMDs alloy materials in the field of high-performance, low-energy ultra-thin optoelectronic devices.

[0003] Controllable synthesis of two-dimensional transition metal chalcogenide alloys is the unremitting pursuit of scientific researchers, and the chemical vapor deposition (CVD) method has been widely used in the synthesis of high-quality 2D TMDs alloy crystals. However, when the CVD method grows TMC alloy materials for high-temperature resistant flexible devices, it is necessary to transfer the TMC alloy materials from a rigid substrate to a high-temperature resistant flexible substrate (such as mica). The existing dry and wet transfer technologies will cause the TMC alloy materials to be contaminated and damaged to varying degrees during the transfer process, which increases the defects of the TMC alloy materials and greatly affects the performance of the device. Therefore, it is still a challenge to directly prepare high-precision, programmable, and patterned wafer-level 2D TMDs alloy materials on high-temperature resistant flexible substrates. CN113088922A discloses a method for preparing and applying a wafer-level absolute monolayer transition metal chalcogenide. The maximum size of the molybdenum tungsten sulfur alloy material prepared by the method is only 80μm. CN110565052A discloses a method for preparing a two-dimensional tungsten sulfide-based vertical heterostructure material. The preparation process of this method is complicated, the preparation process is difficult, the preparation speed is slow, and the cost is high. Therefore, the art urgently needs a method for preparing a molybdenum-tungsten-sulfur alloy material with a simple process, fast preparation speed, and the ability to directly prepare patterned, high-quality, large-area patterns on a high-temperature resistant flexible substrate, and to effectively adjust the component range in the alloy. Summary of the invention

[0004] The purpose of the present invention is to provide a molybdenum-tungsten-sulfur alloy film on a high-temperature resistant substrate and a preparation method thereof. The two-dimensional molybdenum-tungsten-sulfur alloy film material prepared by the present invention is directly prepared on the high-temperature resistant substrate, avoiding various contaminations and damages that the material may suffer during the transfer process.

[0005] To achieve this goal, the following steps need to be implemented:

[0006] A method for preparing a molybdenum-tungsten-sulfur alloy film comprises: using mica as a substrate; mixing a reaction source and a stabilizer in an organic solvent to form a precursor solution, and spin-coating the precursor solution on the substrate surface until the organic solvent evaporates to obtain a precursor film; stacking two mica substrates with precursor films on their surfaces face to face; and performing laser direct writing processing on the stacked mica substrates using a laser direct writing technique to obtain a two-dimensional molybdenum-tungsten-sulfur alloy film on the lower mica substrate.

[0007] Optionally, the parameters of the laser direct writing process include: working distance of 100 to 120 mm; laser power of 2 to 5 W; pulse frequency of 20 to 200 kHz; laser spacing of 1 to 100 μm; and writing speed of 0.1 to 1 m / s.

[0008] Optionally, the parameters of the laser direct writing process include: working distance of 115 mm, laser power of 3 W; pulse frequency of 170 to 200 kHz; laser spacing of 1 to 2 μm, and writing speed of 750 to 900 mm / s.

[0009] Optionally, the reaction source is ammonium tetrathiomolybdate and ammonium tetrathiotungstate;

[0010] The stabilizer is n-butylamine or ethanolamine;

[0011] The organic solvent is dimethylformamide or ethylene glycol.

[0012] Optionally, the ratio of ammonium tetrathiomolybdate to ammonium tetrathiotungstate in the reaction source is 1:(0.1-10), which can be adjusted arbitrarily according to the required alloy ratio.

[0013] Optionally, the concentration of the reaction source is 6-10 mg / ml, the stabilizers n-butylamine and ethanolamine are 1-2 parts each, and the organic solvent is 4-8 parts.

[0014] Optionally, the reaction source and the stabilizer are mixed in an organic solvent and subjected to magnetic stirring and ultrasonic treatment, the magnetic stirring speed is 500-1500 rpm, the stirring time is 10-120 min; and the ultrasonic treatment time is 10-120 min.

[0015] Optionally, the mica substrate is also cleaned by UV / ozone, the UV / ozone cleaning power is 10 to 100 W, and the cleaning time is 50 to 180 seconds.

[0016] Optionally, the organic solvent is evaporated at a temperature of 60 to 180° C. for a time of 1 to 30 minutes.

[0017] A molybdenum-tungsten-sulfur alloy film is prepared by the method for preparing the molybdenum-tungsten-sulfur alloy film of the present invention.

[0018] The advantages of the present invention are:

[0019] 1. The two-dimensional molybdenum-tungsten-sulfur alloy thin film material prepared by the present invention is directly prepared on a high-temperature resistant substrate, thereby avoiding various contaminations and damages that may be caused to the material during the transfer process;

[0020] 2. The two-dimensional molybdenum-tungsten-sulfur alloy thin film material prepared by the present invention has high quality and large area, and the material size can reach the centimeter level;

[0021] 3. The preparation method adopted by the present invention has a simple preparation process and a fast preparation speed, and can realize batch preparation of materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0023] Figure 1 Schematic diagrams of laser direct writing of the embodiments and comparative examples of the present invention (Figure a shows that two thin film substrates with one side coated with solution are stacked on each other and placed in a laser direct writing device; Figure b shows that a mica substrate with one side coated with solution facing upward is directly placed in a laser direct writing device; Figure c shows that a mica substrate with one side coated with solution facing downward is inverted on a silicon dioxide / silicon wafer and placed in a laser direct writing device; Figure d shows that a mica substrate with one side coated with solution facing upward is placed on top of a 1 cm thick glass plate and placed in a laser direct writing device);

[0024] Figure 2 This is a low-magnification optical photograph of the Mo1-xWxS2 film in Example 1 of the present invention;

[0025] Figure 3 This is a high-magnification optical photograph of the Mo1-xWxS2 film in Example 1 of the present invention;

[0026] Figure 4 is the Raman spectrum of the Mo1-xWxS2 thin film in Example 1 of the present invention;

[0027] Figure 5This is a high-magnification optical photograph of the Mo1-xWxS2 film in Example 2 of the present invention;

[0028] Figure 6 is the Raman spectrum of the Mo1-xWxS2 thin film in Example 2 of the present invention;

[0029] Figure 7 This is a high-magnification optical photograph of the Mo1-xWxS2 film in Example 3 of the present invention;

[0030] Figure 8 is the Raman spectrum of the Mo1-xWxS2 thin film in Example 3 of the present invention;

[0031] Fig. 9 This is a high-magnification optical photograph of the film in Comparative Example 1 of the present invention;

[0032] Fig.10 is the Raman spectrum of the thin film in Comparative Example 1 of the present invention;

[0033] Fig.11 This is a high-magnification optical photograph of the film in Comparative Example 2 of the present invention;

[0034] Fig.12 It is the Raman spectrum of the thin film in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are clearly and completely described below in conjunction with the accompanying drawings.

[0036] In order to overcome the shortcomings of the prior art that it is impossible to directly prepare a large area on the surface of a transparent flexible substrate, the number of layers is uncontrollable, the preparation rate is low, and the environmental requirements are high, the present invention provides a molybdenum, tungsten, and sulfur alloy film, a preparation method, an application, and a flexible high-temperature resistant sensor. This experiment can be directly prepared on the surface of a high-temperature resistant substrate, the process is simple, the material is not easily contaminated, and the prepared two-dimensional molybdenum, tungsten, and sulfur alloy material has a large area and good quality.

[0037] Specifically: The preparation of molybdenum tungsten sulfur alloy film includes:

[0038] (1) Laser direct writing preparation of two-dimensional molybdenum, tungsten and sulfur alloy thin film materials. The two-dimensional material is prepared by laser direct writing technology. The reaction source and stabilizer are added to the organic mixed solvent, and the solution is subjected to magnetic stirring for a period of time and then ultrasonic treatment is performed. The mica substrate is cleaned and the prepared solution is spin-coated on the mica surface. After the solvent is evaporated, the two film substrates are stacked on one side with the solution spin-coated on the other side, placed in a laser direct writing device, and the laser parameters are adjusted. After the laser direct writing is completed, a large area of ​​two-dimensional molybdenum, tungsten and sulfur alloy thin film material can be obtained on the lower mica surface. The molybdenum source, tungsten source and sulfur source in step (1) are ammonium tetrathiomolybdate and ammonium tetrathiotungstate. The organic mixed solvent in step (1) is dimethylformamide, ethylene glycol, etc.; the stabilizer is n-butylamine, ethanolamine, etc. Preferably, dimethylformamide is used as the organic solvent, and n-butylamine and ethanolamine are used as stabilizers. The magnetic stirring speed in step (1) is 500-1500 rpm, and the stirring time is 10-120 min, preferably the magnetic stirring speed is 1500 rpm, and the stirring time is 120 min. The ultrasonic treatment time in step (1) is 10-120 min, and preferably the ultrasonic time is 120 min. The UV / ozone cleaning power in step (1) is 10-100 W, and the cleaning time is 50-180 s. Preferably, the cleaning power is 100 W, and the cleaning time is 180 s. The hot plate baking temperature in step (1) is 60-180° C., and the time is 1-30 min. In step (1), the two mica substrates with the sides coated with the solution are stacked relative to each other. The working distance in the laser parameters in step (1) is 100-120 mm; the laser power is 2-5 W; the pulse frequency is 20-200 kHz; the laser spacing is 1-100 μm; and the writing speed is 0.1-1 m / s.

[0039] The thickness of the film prepared by this method is controllable and uniform. Due to the fast laser heating speed, the material preparation speed is very fast. Laser heating causes thermal decomposition of the precursor, and a large amount of reducing gas and sulfur atoms are generated in the process, which hinders the Mo 1-x W x The reaction of S2 film with air can make Mo directly prepared in air. 1-x W x In addition, there are a large number of tiny grain boundaries and cracks in the S2 material during the preparation process, which helps to enhance the Mo 1-x W x The responsiveness of S2 material as a sensor. In addition, patterned sensor preparation can be realized through programming, and the industrial preparation of different patterned thin film sensors can be realized.

[0040] Embodiment 1:

[0041] 18.06 mg of ammonium tetrathiomolybdate and 96.56 mg of ammonium tetrathiotungstate were dissolved in a mixed solution of 5 ml of dimethylformamide solution, 4 mL of ethanolamine and 4 mL of n-butylamine, and magnetically stirred at 1500 rpm for 120 min, and further ultrasonically stirred for 120 min. At the same time, the mica substrate was plasma cleaned for 3 min at 100 W power under ozone / oxygen plasma. The precursor solution was spin-coated on the plasma-cleaned mica surface in a gradient program (500 rpm for 5 s, 1500 rpm for 30 s), and baked on a hot plate at 150 ° C for 3 min to evaporate the residual solvent. The two thin film substrates with the sides coated with the solution were stacked on each other and placed in a laser direct writing device, such as Figure 1 As shown in a. At 70mm 2 Under the field mirror, the working distance was adjusted to 115 mm, the laser power was 3 W, the pulse frequency was 200 kHz, the laser spacing was 1 μm, and the writing speed was 750 mm / s. 1-x W x Low-magnification optical photographs of S2 alloy films are shown in Figure 2. Figure 2 As shown, high-magnification optical photos are Figure 3 As shown, the Raman spectrum is Figure 4 As shown, the results show that the centimeter-scale Mo 1-x W x S2 alloy material.

[0042] Embodiment 2:

[0043] 18.06 mg of ammonium tetrathiomolybdate and 96.56 mg of ammonium tetrathiotungstate were dissolved in a mixed solution of 5 ml of dimethylformamide solution, 4 mL of ethanolamine and 4 mL of n-butylamine, and magnetically stirred at 1500 rpm for 120 min, and further ultrasonically stirred for 120 min. At the same time, the mica substrate was plasma cleaned for 3 min at 100 W power under ozone / oxygen plasma. The precursor solution was spin-coated on the plasma-cleaned mica surface in a gradient program (500 rpm for 5 s, 1500 rpm for 30 s), and baked on a hot plate at 150 ° C for 3 min to evaporate the residual solvent. The two thin film substrates with the sides coated with the solution were stacked on each other and placed in a laser direct writing device, such as Figure 1 As shown in a. At 70mm 2 Under the field mirror, the working distance was adjusted to 115 mm, the laser power was 3 W, the pulse frequency was 170 kHz, the laser spacing was 2 μm, and the writing speed was 750 mm / s. 1-x W x S2 alloy film Figure 5 As shown, the Raman spectrum is Figure 6 As shown, it shows that the synthesized material is Mo 1-x W xS2 alloy.

[0044] Embodiment three:

[0045] 18.06 mg of ammonium tetrathiomolybdate and 96.56 mg of ammonium tetrathiotungstate were dissolved in a mixed solution of 5 ml of dimethylformamide solution, 4 mL of ethanolamine and 4 mL of n-butylamine, and magnetically stirred at 1500 rpm for 120 min, and further ultrasonically stirred for 120 min. At the same time, the mica substrate was plasma cleaned for 3 min at 100 W power under ozone / oxygen plasma. The precursor solution was spin-coated on the plasma-cleaned mica surface in a gradient program (500 rpm for 5 s, 1500 rpm for 30 s), and baked on a hot plate at 150 ° C for 3 min to evaporate the residual solvent. The two thin film substrates with the sides coated with the solution were stacked on each other and placed in a laser direct writing device, such as Figure 1 As shown in a. At 70mm 2 Under the field mirror, the working distance was adjusted to 115 mm, the laser power was 3 W, the pulse frequency was 200 kHz, the laser spacing was 2 μm, and the writing speed was 900 mm / s. 1-x W x S2 alloy film Figure 7 As shown, the Raman spectrum is Figure 8 As shown, it shows that the synthesized material is Mo 1-x W x S2 alloy.

[0046] Embodiment 4: (Comparative Example 1).

[0047] 18.06 mg of ammonium tetrathiomolybdate and 96.56 mg of ammonium tetrathiotungstate were dissolved in a mixed solution of 5 ml of dimethylformamide solution, 4 mL of ethanolamine and 4 mL of n-butylamine, and magnetically stirred at 1500 rpm for 120 min, and further ultrasonically stirred for 120 min. At the same time, the mica substrate was plasma cleaned for 3 min at 100 W power under ozone / oxygen plasma. The precursor solution was spin-coated on the plasma-cleaned mica surface in a gradient program (500 rpm for 5 s, 1500 rpm for 30 s), and baked on a hot plate at 150 ° C for 3 min to evaporate the residual solvent. The two thin film substrates with the sides coated with the solution were stacked on each other and placed in a laser direct writing device, such as Figure 1 As shown in a. At 70mm 2 Under the field mirror, the working distance was adjusted to 130 mm, the laser power was 3 W, the pulse frequency was 200 kHz, the laser spacing was 1 μm, and the writing speed was 750 mm / s. 1-x W x S2 alloy film Fig. 9 As shown, the Raman spectrum is Fig.10As shown, it shows that the synthesized material is MoS2, and Mo is not synthesized. 1-x W x S2 alloy.

[0048] By comparison, it can be shown that when the laser parameters are not within the parameter range given in the claims of the present invention and other conditions remain unchanged, a large-area two-dimensional molybdenum-tungsten-sulfur alloy thin film material cannot be synthesized on the substrate.

[0049] Embodiment 5: (Comparative Example 2).

[0050] 18.06 mg of ammonium tetrathiomolybdate and 96.56 mg of ammonium tetrathiotungstate were dissolved in a mixed solution of 5 ml of dimethylformamide solution, 4 mL of ethanolamine and 4 mL of n-butylamine, and magnetically stirred at 1500 rpm for 120 min, and further ultrasonically stirred for 120 min. At the same time, the mica substrate was plasma cleaned for 3 min at 100 W power under ozone / oxygen plasma. The precursor solution was spin-coated on the plasma-cleaned mica surface in a gradient program (500 rpm for 5 s, 1500 rpm for 30 s), and baked on a hot plate at 150 ° C for 3 min to evaporate the residual solvent. The mica substrate was turned upside down on the silicon dioxide / silicon wafer with the side of the mica substrate spin-coated with the solution facing down, and placed in a laser direct writing device, such as Figure 1 c. At 70mm 2 Under the field mirror, the working distance was adjusted to 115 mm, the laser power was 3 W, the pulse frequency was 200 kHz, the laser spacing was 2 μm, and the writing speed was 750 mm / s. 1-x W x S2 alloy film Fig.11 As shown, the Raman spectrum is Fig.12 As shown, it shows that Mo is not synthesized 1-x W x S2 alloy.

[0051] By comparison, it can be shown that when the substrate stacking method does not use the method given by the present invention, under the condition that other conditions remain unchanged, a large-area two-dimensional molybdenum-tungsten-sulfur alloy thin film material cannot be synthesized on the substrate.

[0052] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0053] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0054] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a molybdenum-tungsten-sulfur alloy film, characterized in that: include: Mica is used as the substrate; A reaction source and a stabilizer are mixed in an organic solvent to form a precursor solution, and the precursor solution is spin-coated on a substrate surface until the organic solvent evaporates to obtain a precursor film; Two mica substrates with precursor films on their surfaces are stacked face to face; By using laser direct writing technology to process the stacked mica substrates with laser direct writing, a two-dimensional molybdenum-tungsten-sulfur alloy film can be obtained on the lower mica substrate. The parameters of the laser direct writing process include: working distance of 100-120 mm; laser power of 2-5 W; pulse frequency of 20-200 kHz; laser spacing of 1-100 μm; writing speed of 0.1-1 m / s; The reaction source is ammonium tetrathiomolybdate and ammonium tetrathiotungstate; the stabilizer is n-butylamine or ethanolamine; the organic solvent is dimethylformamide or ethylene glycol; The ratio of ammonium tetrathiomolybdate to ammonium tetrathiotungstate in the reaction source is 1:(0.1-10); The concentration of the reaction source is 6-10 mg / ml, the stabilizers n-butylamine and ethanolamine are 1-2 parts each, and the organic solvent is 4-8 parts; The organic solvent evaporation temperature is 60-180° C. and the evaporation time is 1-30 minutes.

2. The method for preparing a molybdenum-tungsten-sulfur alloy thin film according to claim 1, characterized in that: The parameters of the laser direct writing process include: working distance of 115 mm, laser power of 3 W, pulse frequency of 170-200 kHz, laser spacing of 1-2 μm, and writing speed of 750-900 mm / s.

3. The method for preparing a molybdenum-tungsten-sulfur alloy thin film according to claim 1 or 2, characterized in that: The reaction source and the stabilizer are mixed in an organic solvent and subjected to magnetic stirring and ultrasonic treatment. The magnetic stirring speed is 500-1500 rpm, the stirring time is 10-120 min, and the ultrasonic treatment time is 10-120 min.

4. The method for preparing a molybdenum-tungsten-sulfur alloy thin film according to claim 1 or 2, characterized in that: The mica substrate is also cleaned by UV / ozone, with the UV / ozone cleaning power ranging from 10 to 100 W and the cleaning time ranging from 50 to 180 s.

5. A molybdenum-tungsten-sulfur alloy film, characterized in that: The molybdenum-tungsten-sulfur alloy film is prepared by the method for preparing the molybdenum-tungsten-sulfur alloy film according to any one of claims 1 to 4.